Partnerships in care: qualitative analysis of different perspectives. (3rd April 2022) - Tluczek, Audrey; Grob, Rachel; Gorp, Stacy Van; Greene, Lisa C.; Yu, Zhiyuan; Raymond, Katherine; Collins, Lauren; George, Cynthia
ABSTRACT: Background: Even with the addition of CFTR-modulator therapies in cystic fibrosis (CF) care, engagement in home treatments by persons with CF (PwCF) and their family caregivers remains key to slowing progression of CF-related complications. Best practice guidelines for home care describe an ideal not necessarily attainable for many PwCF in real life. Effective clinical partnerships between PwCF/their families and clinicians are critical to developing feasible home treatments plans. Method: A team of content and methodology experts conducted a grounded dimensional analysis of transcribed interviews from 20 clinicians and 7 parents of 9 children with CF to identify and describe social processes associated with a clinical partnership. Results: The resulting theoretical framework explicates conceptualizations of partnership (i.e. mutuality and reciprocity) and conditions (i.e. quality and duration of relationship, patient's developmental or life stage) that contribute to the enactment of successful partnerships. Parents recognize their own and clinicians' complementary contributions to partnerships. Clinicians focus on strategies to improve outcomes – some consistent, other discrepant with their conceptualizations of partnership. Participants' reflections of lessons learned from successful versus failed partnerships informed their subsequent enactments of partnerships. Conclusions: Trends in health care delivery show a shift from well-intended, yet paternalistic, paradigms to partnership models in which the complementary expertise of patients and caregivers as well as clinicians are mutually recognized and valued. Our findings show that while parents and clinicians endorse similar philosophical principles of partnership, they differ in how they actually enact them. Transition to a partnership paradigm appears to remain a work in progress.